Proses Berpikir Kritis Siswa Berdasarkan Teori Asimilasi Akomodasi dalam Menyelesaikan Soal Open Ended Materi Aljabar - Dian Farah Putri Mahardika (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The Merdeka Curriculum aims to develop students with strong character who uphold Pancasila values, including critical thinking. This ability is crucial in facing technological and informational advancements and can be assessed through open ended questions. Students' thinking processes in solving these questions relate to the theories of assimilation and accommodation. This study describes students' critical thinking processes based on assimilation-accommodation theory in open ended algebra problems. Using a qualitative descriptive approach, this research analyzes open-ended test results and interviews with three subjects (S1, S2, S3) selected based on their critical thinking abilities (high, medium, low). The results show that S1 relies more on assimilation but can accommodate when evaluating. S2 demonstrates a balance between assimilation and accommodation, with good self-reflection. S3 tends to accommodate more due to greater difficulties but still strives to find solutions.
Reaploud Repository February 2026_Hasyim
Keywords: Critical Thinking; Assimilation; Accommodation; Open-Ended Questions; Merdeka Curriculum